Abuse and Harassment of Female Journalists in Karnali - Joshi, Keshabi Kumari (KMC Journal, 2023)
This study explores the experiences of abuse and harassment faced by female journalists in the Karnali Province. In the base of concurrent research design, mixed method was adopted in this study. For quantitative method, questionnaire was developed and online survey was conducted for data collection. For that 60 respondents were selected. Like that, for qualitative study, focus group discussion and semi-structured interviews were performed. Where 3 senior female journalists were selected for the interview and 10 victims were selected for focus group discussion. This study set up within the theoretical framework of objectification and spiral of silence. Results reveal that patriarchal societal norms contribute to the objectification of female journalists, leading to a high prevalence of abuse that is often not reported due to ineffective laws, discrimination, shame, economic vulnerability, and lack of political access. The result also shows that female journalists often lack self-confidence and may bear the harassment silently or try to hide it due to the fear of social boycott. It highlights the issues of unequal wages, lack of credit for their work, and exploitation by senior journalists.